Phase III randomized pilot study comparing interferon α- 2b in combination with radiation therapy versus radiation therapy alone in patients with stage III-B carcinoma of the cervix. Issue 2 (1st February 2003) - Yazigi, R.; Aliste, G.; Torres, R.; Ciudad, A. M.; Cuevas, M.; Garrido, J.; Prado, S.; Solá, A.; Castillo, R.; Cerda, B.; Cumsille, M. A.; González, M.; et al.
Abstract : This randomized pilot study was designed to determine whether the addition of interferon α-2b to standard radiation therapy offered an advantage in loco-regional control and survival over radiation therapy alone in a homogeneous group of patients with stage IIIB carcinoma of the cervix. Thirty-six patients were treated with a combination of interferon α-2b plus radiation therapy, and 38 patients were treated with radiation therapy alone. Patients with evidence of ureteral obstruction were excluded from the study. Evaluation of loco-regional response was determined by pelvic examination, cervical cytology, biopsies and CT scans when indicated. Survival time was measured from initiation of treatment to date of death or last follow-up. Patient characteristics were comparable between both study arms. The objective complete response rate was 67% in the combined therapy group and 55% in the radiation alone group ( P = 0.454). With a median follow-up of 17 months for all patients and 31 months for live patients, 50% of the combined group survived vs. 39.5% of the radiation alone group ( P = 0.424). We conclude that the addition of interferon α-2b to standard radiation therapy did not significantly improve loco-regional response or survival, although such a trend was noted. We encourage the design of a larger randomized study with sufficient power to detect meaningful differences to prove whether the tendency observed in the present investigation holds any promise to improve the outcome of these patients.